2008
DOI: 10.1073/pnas.0806375105
|View full text |Cite
|
Sign up to set email alerts
|

The replicative DNA polymerase of herpes simplex virus 1 exhibits apurinic/apyrimidinic and 5′-deoxyribose phosphate lyase activities

Abstract: Base excision repair (BER) is essential for maintaining genome stability both to counter the accumulation of unusual bases and to protect from base loss in the DNA. Herpes simplex virus 1 (HSV-1) is a large dsDNA virus that encodes its own DNA replication machinery, including enzymes involved in nucleotide metabolism. We report on a replicative family B and a herpesvirus-encoded DNA Pol that possesses DNA lyase activity. We have discovered that the catalytic subunit of the HSV-1 DNA polymerase (Pol) (UL30) exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Hence, HSV-1 encodes a uracil DNA glycosylase (UDG) (UL2) as well as a dUTPase to reduce the pool of dUTP and prevent misincorporation by the viral Pol (24,25). Moreover, we recently showed that the catalytic subunit of the viral Pol (UL30) exhibits AP and 5Ј-deoxyribose phosphate (dRP) lyase activities (26). The presence of a virus-encoded UDG and DNA lyase indicates that HSV-1 has the capacity to perform integral steps of BER, specifically for the removal of uracil.…”
Section: Herpes Simplex Virus-1 (Hsv-1)mentioning
confidence: 99%
“…Hence, HSV-1 encodes a uracil DNA glycosylase (UDG) (UL2) as well as a dUTPase to reduce the pool of dUTP and prevent misincorporation by the viral Pol (24,25). Moreover, we recently showed that the catalytic subunit of the viral Pol (UL30) exhibits AP and 5Ј-deoxyribose phosphate (dRP) lyase activities (26). The presence of a virus-encoded UDG and DNA lyase indicates that HSV-1 has the capacity to perform integral steps of BER, specifically for the removal of uracil.…”
Section: Herpes Simplex Virus-1 (Hsv-1)mentioning
confidence: 99%
“…The antiviral compound acyclovir is incorporated less efficiently than dGTP but causes chain termination, and it is removed with a half-life of 1 h (36). Interestingly, the polymerase can cleave an apurinic/apyrimidinic site in duplex DNA as well as remove the product 5Ј-deoxyribose phosphate by a lyase activity (37). The presence of a separate UL2 uracil glycosylase as well as apurinic/apyrimidinic and 5Ј-deoxyribose phosphate lyase activities in the virus polymerase indicates important roles in enhancing replication fidelity (17).…”
Section: Properties Of Replisome Proteinsmentioning
confidence: 99%
“…The enzyme forms a complex with the viral DNA polymerase and collaborates to perform DNA repair (37). The presence of a dUTPase and a ribonucleotide reductase lacking allosteric control mechanisms may indicate an enhanced risk for misincorporation of dNTPs during replication (35).…”
Section: Repair and Recombination Of Hsv-1 Dnamentioning
confidence: 99%
“…The extreme C terminus of HSV-1 Pol is crucial for an interaction with processivity factor UL42 that is necessary for long-chain DNA synthesis and indispensable for viral replication (11). Most recently, HSV-1 Pol was found to possess apurinic/apyrimidinic and 5=-deoxyribose phosphate lyase activities consistent with base excision repair processes, which are typically functions of the repair polymerase family X (3,35). Although the active site has yet to be mapped, DNA lyase activity has been localized to a 63-kDa C-terminal fragment of HSV-1 Pol (3).…”
mentioning
confidence: 99%